PENGEMBANGAN PROFESI DOSEN DI FAKULTAS TARBIYAH IAIN SUNAN AMPEL SURABAYA - Sri Abidah Suryaningsih, ; Arif Mustofa, (Pelangi Ilmu, 2009)
Abstraction :The purpose of this research is to develop the lecturers profession, to describe the lecturers perception, and to describe the proponent factors and the resistor factors of the development of lecturers profession. The type of this research is qualitative positivistic. The result of this theis shows that the lecturers become more dynamic and more autonomic, while the profession organization is developed in a small scale. The lecturers perception become more enthusiastic. The proponent factors are the young lecturers and the facilities. The resistor factors are the workdload of the lecturers, the lack of the fund, and the less harmonious communications. In its development, the resistor factors are minimized and the proponent factors are improved more.